2015
DOI: 10.3928/01484834-20150814-05
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Education Transformation: Promising Practices in Academic Progression

Abstract: This article summarizes that process and provides a description of the models, challenges, common themes, recommendations, and progress to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Educators emphasized crafting program plans to integrate the curriculum and a seamless transition for students from ADN to BSN [9,12,15]. Eliminating curricular redundancies was of primary concern [17]. Sharpnack et al [15] reported using gap analysis to assist faculty in identifying strengths, weaknesses, and overlaps of each partner curriculum before devising program pathways.…”
Section: Program Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Educators emphasized crafting program plans to integrate the curriculum and a seamless transition for students from ADN to BSN [9,12,15]. Eliminating curricular redundancies was of primary concern [17]. Sharpnack et al [15] reported using gap analysis to assist faculty in identifying strengths, weaknesses, and overlaps of each partner curriculum before devising program pathways.…”
Section: Program Developmentmentioning
confidence: 99%
“…Bopp and Einhellig [6] reported the importance of detailing student prerequisite and admission requirements, program policies, and progression pathways. Several institutions ran small pilot studies before instituting full program enrollment [10,11], and others sought the advice of experts or consultants to help with the development and implementation of programs [17].…”
Section: Program Developmentmentioning
confidence: 99%
“…The purpose of nursing education is to create critical and creative thinking, promote spontaneous learning, enhance psychomotor skills, promote time management, increase self‐confidence, improve appropriate communication and prevent students’ passivity (Aliafsari Mamaghani et al ; Sezer ). Therefore, it can be stated that nursing practice depends on the quality of nursing education for training students with the ability to provide standard health care to patients in various health environments (Gorski et al ; Ortega et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The question remains whether or not nursing education has met that challenge in the intervening years. Recent publications (Adams, 2014; Benner, 2012; Gorski, Farmer, Sroczynski, Close, & Wortock, 2015) continue to call for a transformation in nurse education to meet requirements in a variety of healthcare settings. Gorski and colleagues noted that “health care has changed over the past decade; yet nursing education has not kept pace with social and scientific advances” (p. 509).…”
mentioning
confidence: 99%